Toxicity of depleted uranium on isolated rat kidney mitochondria - Shaki, Fatemeh; Hosseini, Mir-Jamal; Ghazi-Khansari, Mahmoud; Pourahmad, Jalal (Biochimica et biophysica acta, 2012)
Kidney is known as the most sensitive target organ for depleted uranium (DU) toxicity in comparison to other organs. Although the oxidative stress and mitochondrial damage induced by DU has been well investigated, the precise mechanism of DU-induced nephrotoxicity has not been thoroughly recognized yet. Kidney mitochondria were obtained using differential centrifugation from Wistar rats and mitochondrial toxicity endpoints were then determined in both in vivo and in vitro uranyl acetate (UA) exposure cases. Single injection of UA (0, 0.5, 1 and 2mg/kg, i.p.) caused a significant increase in blood urea nitrogen and creatinine levels. Isolated mitochondria from the UA-treated rat kidney showed a marked elevation in oxidative stress accompanied by mitochondrial membrane potential (MMP) collapse as compared to control group. Incubation of isolated kidney mitochondria with UA (50, 100 and 200μM) manifested that UA can disrupt the electron transfer chain at complex II and III that leads to induction of reactive oxygen species (ROS) formation, lipid peroxidation, and glutathione oxidation. Disturbances in oxidative phosphorylation were also demonstrated through decreased ATP concentration and ATP/ADP ratio in UA-treated mitochondria. In addition, UA induced a significant damage in mitochondrial outer membrane. Moreover, MMP collapse, mitochondrial swelling and cytochrome c release were observed following the UA treatment in isolated mitochondria. Both our in vivo and in vitro results showed that UA-induced nephrotoxicity is linked to the impairment of electron transfer chain especially at complex II and III which leads to subsequent oxidative stress. ► Depleted uranium caused mitochondrial dysfunction after vivo and in vitro treatment. ► Depleted uranium inhibited complex II and III of mitochondrial respiratory chain. ► Respiratory chain disruption increased oxidative stress markers in mitochondria. ► Depleted uranium caused mitochondrial permeability transition and cytochrome c release. ► Depleted uranium induced cytochrome c release from mitochondria.